Effects of water storage on seed germination and seedling growth of rubber (Hevea brasiliensis Muell Arg.) - Mercykutty V C; Premakumary D; Saraswathyamma C K; Thomas V (Planter, 1996)
Fresh rubber seeds stored under ambient conditions in water gave 45 perr cent germination even after 20 days as compared to zero germination o fseeds stored under open air conditions. The water storage treatment was better than the open air storage for seed moisture content, germination percentage and all growth attributes except for number of lateral roots.
Keywords: Germination percentage; Rubber seeds; Water storage